Profile of vitiligo in Kumaun region of Uttarakhand, India - Saurabh Agarwal; Amit Ojha; Shalini Gupta (Wolters Kluwer Medknow Publications, 2014)
Background: Vitiligo is a common, acquired, pigmentary disorder characterized by loss of melanocytes resulting in white spots. This disease carries a lot of social stigma in India. Objective: To study the clinico-epidemiological profile of vitiligo patients in Kumaun region of Uttarakhand state in India. Materials and Methods: The clinical presentation of vitiligo was examined and analyzed in 762 vitiligo patients attending the Dermatology outdoor of Government Medical College, Haldwani, which is a referral centre for Kumaun region of Uttarakhand state in India. Results: Male and female patients were found to be affected almost equally. It was observed that onset of vitiligo was most common in 0-10 years age group, as evidenced by 336 cases out of 762 cases. Acrofacial type of vitiligo (339 cases out of 762) was most commonly observed, followed by vitiligo vulgaris, focal, segmental, mucosal, mixed, and universal vitiligo. The most common site of onset was the lower limbs followed by head and neck, upper limbs, trunk, genitalia, and mucasae. Leucotrichia was observed in 33.5%, Koebner's phenomenon in 26.3%, and a positive family history in 19% of the vitiligo patients. The other common conditions associated were thyroid disorders (8.9%), diabetes (5.3%), and atopic dermatitis (4.9%). Conclusion: The study indicates that acrofacial vitiligo is the most common clinical type observed in Kumaun region of Uttarakhand in India. Onset of vitiligo is most common in first decade of life.